The Role of the Liver in Iron Homeostasis and What Goes Wrong? (Journal of Renal and Hepatic Disorders, 2021)
Iron is an essential mineral that is vital for growth development, normal cellular function, synthesis of hormones and connective tissue, and most importantly, serves as a component of hemoglobin to carry oxygen to body tissues. The body finely regulates the amount of circulating and stored iron within the body to maintain concentration levels within range for optimal physiologic function. Without iron, the ability for cells to participate in electron transport and energy metabolism decreases. Furthermore, hemoglobin synthesis is altered, which leads to anemia and decreased oxygen delivery to tissue. Problems arise when there is too little or too much iron. This review explores the role of the liver in iron physiology, iron overload and discusses the most common causes of primary and secondary hepatic iron overload.
Keywords: liver; iron homeostasis; iron overload